2011
DOI: 10.1124/mol.111.072546
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-Selective Inhibition of Phosphoinositide 3-Kinase: Identification of a New Region of Nonconserved Amino Acids Critical for p110α Inhibition

Abstract: The combination of molecular modeling and X-ray crystallography has failed to yield a consensus model of the mechanism for selective binding of inhibitors to the phosphoinositide 3-kinase (PI3K) p110 ␣-isoform. Here we have used kinetic analysis to determine that the p110␣-selective inhibitor 2-methyl-5-nitro-2-[(6-bromoimidazo[1,2-␣]pyridin-3-yl)methylene]-1-methylhydrazide-benzenesulfonic acid (PIK-75) is a competitive inhibitor with respect to a substrate, phosphatidylinositol (PI) in contrast to most other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 25 publications
5
39
0
2
Order By: Relevance
“…The PI3K pathway regulates cellular functions relevant to tumourogenesis, but unfortunately, clinical studies of broad PI3K inhibitors have been plagued by toxicity (Zheng et al, 2011). More specific approaches to inhibit specific isoforms in MM were performed; PI3KCD was inhibited using the specific inhibitor CAL-101, which overcame MM cell growth conferred by IL6, IGF1, and bone marrow stromal cell coculture .…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K pathway regulates cellular functions relevant to tumourogenesis, but unfortunately, clinical studies of broad PI3K inhibitors have been plagued by toxicity (Zheng et al, 2011). More specific approaches to inhibit specific isoforms in MM were performed; PI3KCD was inhibited using the specific inhibitor CAL-101, which overcame MM cell growth conferred by IL6, IGF1, and bone marrow stromal cell coculture .…”
Section: Discussionmentioning
confidence: 99%
“…Only 2-methyl-5-nitro-2-[(6-bromoimidazo[1,2-a]pyridin-3-yl)methylene]-1-methylhydrazide-benzenesulfonic acid (PIK-75; refs. 23,24) and NCGC00012848-02 (NIH-12848; ref. 25) have been identified as substrate-competitive inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…MD simulation and its subsequent studies provided valuable tools for the development of isoform-specific PI3K inhibitors, complementing the molecular modeling method [151]. It has been reported that the combinatory effort of comparative molecular field analysis (CoMFA), comparative molecular similarity induces analysis (CoMSIA), docking analysis and MD simulation can elucidate the structure-activity correlation of the inhibitors of p110α, as well as the binding modes of inhibitors at the ATP binding pocket [152].…”
Section: Molecular Dynamics Simulation Inspires a New Generation Omentioning
confidence: 99%